Part-time employment in Britain and Japan : a comparative study of legal discourse - Shima, Satomi (1997)
This study analyses the discursive construction of part-time employment and the workers in it in the employmentand legal contexts in Britain and Japan, applying an analytical framework of the law developed from a post-structuralist feminist viewpoint. In doing this, this study contributes to knowledge in the field of legal studies by providing an account of the active role of the law in the area of employment,through the operation of discourse, in shaping and reshaping structural inequality which part-time women employees face in contemporary British and Japanese society. Evidence for this study is collected from statistical data, questionnaires and interviews with managers, interviews with a group of ex-part-time women workers pursuing a legal case and the close reading of legal materials in the two countries. From the examination of these data, two discourses are identified,which circulate in employment and legal institutions in both countries and which help to produce the differentiation between full-time and part-time employees. One discourse emphasises differencesin labour-related factors, such as working hours, job content and commitment, while the other emphasises differences in the gendered characteristics and domestic positions of men and women. I show that the two discourses operate within and across these institutions, constructing part-time employment as different from and inferior to full-time employment on both labour related and gender-related grounds, and legitimisingthe disadvantaged position of part-time employees. This discursive construction has brought about a gendered hierarchy within the law in which the inferior working pattern of part-time employment is gendered as women's, while the superior pattern of full-time employmentis gendered as men's. On the basis of this analysis, I argue that the law is one of the most influential discursive mechanisms which bring about and help to sustain the hierarchical gendering of society, contributing to the production and reproduction of unequal power relations between the sexes and between employers and part-time women employees.